Pengaruh Content Marketing terhadap Keputusan Pembelian Pakaian di Shopee Live - Debora Christine Girsang; Aprinawati Aprinawati (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to determine the influence of content marketing on clothing purchasing decisions at Shopee Live for students majoring in management, Faculty of Economics, Medan State University, Stambuk 2020. This research uses quantitative descriptive methods using simple linear regression analysis techniques and the data is analyzed using the SPSS 24.0 program. From the results of the analysis, it can be seen that content marketing has a positive and significant effect on the decision to purchase clothes at Shopee Live for students majoring in management, Faculty of Economics, Medan State University, Stambuk 2020, this is in accordance with the results of calculations in the partial test/t test, the calculated t value is > t table. namely 7.871 > 1.1996 so that the significant value is 0.000 < 0.05. So it is concluded that Content Marketing (X) has a positive and significant effect on Purchasing Decisions (Y).